2019
DOI: 10.3390/molecules24091811
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Selecting “Q-Markers” of Chinese Medical Preparation via Components Transfer Process Analysis with Application to the Quality Control of Shengmai Injection

Abstract: Chinese medical preparation has complicated chemical constituents. Consequently, the proper quality control methods for these Chinese medical preparations have been great challenges to the traditional Chinese medicine modernization and internationalization. What components should be chosen for quality control is a big challenge in the development of traditional Chinese medicine. A new concept of “Quality Marker” was proposed by Liu et al. to solve this problem and established a new research paradigm for tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…It is widely used in the traceability system of quality process control. Zhao [16] screened Q-markers using the strategy of analyzing the transfer of compounds in shengmai injection, and applied the results for quality control. Moreover, Liao [17] applied chemical analysis and network pharmacology for screening Q-markers of Alisma orientale.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used in the traceability system of quality process control. Zhao [16] screened Q-markers using the strategy of analyzing the transfer of compounds in shengmai injection, and applied the results for quality control. Moreover, Liao [17] applied chemical analysis and network pharmacology for screening Q-markers of Alisma orientale.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al identified or partially characterized 87 herbal compounds in SMI and selected 6 bioactive constituents (four ginsenosides (i.e., Rg 1 , Re, Rb 1 , and Rd) and 2 lignans (i.e., schisandrol A and schisandrol B) with high content levels as quality markers (Q-markers). The total content range for these selected Q-markers in 10 batches of SMI was 13.8-22.5 mg/mL [182]. Wu et al identified 92 compounds (i.e., 49 ginsenosides, 31 lignans, 5 steroidal saponins, and 7 homoisoflavanones) in SMP and discovered a class of 25-hydroxyginsenosides for the first time [183].…”
Section: Shengmai Formulamentioning
confidence: 99%
“…8,12 In addition, a few studies determined the contents of steroid saponins and saccharides of Shengmai preparations by using an evaporative light scattering detector (ELSD). 13 Quantitative analysis method were mainly focused on the a single marker or a few markers, which is not enough to reflect and control the quality of Shengmai preparations. 12 While fingerprints can comprehensively reflect the overall chemical composition characteristics of traditional Chinese medicine and have been widely used.…”
Section: Introductionmentioning
confidence: 99%
“…However, only ionized compounds can be detected, and the comparatively high detection cost is the limitation of MS. 12 Furthermore, the HPLC-ELSD technique was also utilized to detect saponins and sugars in the preparations. 13,15 However, the methods could not provide high-efficiency analysis due to low sensitivity and the narrow linear range. 13,16 Moreover, some researchers have used charged aerosol detectors (CADs) to detect the carbohydrates in the Yiqifumai lyophilized injections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation